Perception Analysis of Accounting Education Students on Teaching Performance of Lecturers in Online Learning during Covid-19 - Harsono, H; Buana, Dewangga Satria; Narimo, Sabar (Universitas Muhammadiyah Surakarta, 2022)
The covid-19 pandemic has affected all sectors of life, including education. The education system during the COVID-19 pandemic was implemented by distance learning or online learning, which required students and lecturers to master information technology. The purpose of the research is to find out how the impact and application of online learning is in the Accounting Education Study Program, Universitas Muhammadiyah Surakarta, as well as to find out student responses regarding lecturers' teaching performance during online learning during the covid- 19 pandemics. This study uses qualitative research with data collection techniques by observation, interviews, and documentation. The results of the study show that the situation of lecturers who experience changes in teaching performance has an effect on student learning outcomes.